Design and Development of a Hybrid Tricopter Fixed-Wing UAV for Precision Agriculture - Febrianto, Rokhmat; Yeoh, Jessie Charydon; Putra, I Gede Arinata Kusuma; Sasmito, Ayomi; Alfiansyah, Agung (AI Society & STMIK Indonesia, 2024)
Precision Agriculture (PA) relies on innovative technologies to enhance efficiency and sustainability in agricultural practices. This study focuses on the design, simulation, and evaluation of a Hybrid Tricopter VTOL UAV tailored for PA applications. The UAV combines hover and fixed-wing flight modes, enabling versatility in data collection and farmland monitoring. Through rigorous simulations, the hover mission demonstrated the effectiveness of PID controllers in stabilizing roll, pitch, and yaw dynamics, achieving high positional accuracy with minimal error rates. The transition mission validated the UAV’s adaptability, showcasing smooth transitions between flight modes under varying tilt rates. Additionally, electronic component simulations confirmed the propulsion system operates efficiently within thermal and electrical limits, ensuring durability and energy efficiency. The findings highlight the UAV’s reliability, adaptability, and operational readiness, laying a foundation for advanced UAV applications in PA and beyond. This work underscores the potential of UAVs in optimizing agricultural productivity and sustainability.